Fully Cancellation and Naturally Cancellation Modules - Hadi, Inaam M A; Elewi, Alaa A (Al-Nahrain Journal of Science, 2018)
In this paper, we introduce two types of cancellation modules namely fully cancellation and naturally cancellation. Some characterizations of these concepts are given and some properties of these concepts in the class of multiplication modules are presented. Also the direct sum of fully cancellation module and the behaviour of fully cancellation (naturally cancellation) are discussed.